(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In order to compete in the ever-growing competent market it is very important for a structural engineer to save time. As a sequel to this an attempt is made to analyze and design a multistoried residential building by using a software package STAAD.Pro. For analyzing a multi storied building one has to consider all the possible loadings and see that the structure is safe against all possible loading conditions. The present project deals with the analysis and design of a multi storied residential building of G+3. The dead load, live loads and wind loads are applied and the design for beams and columns is obtained STAAD.Pro with its new features surpassed its predecessors and compotators with its data sharing capabilities with other major software like AutoCAD.